Preliminary sizing and study of a hybrid rocket based combined cycle - Hillion, Laurine; Parisse, Jean-Denis; Mangeot, Alexandre (Frontiers in Space Technologies, 2023)
In order to provide a competitive advantage over existing platforms, the interest of a missile propelled by a RBCC (for Rocket Based Combined Cycle) engine has been investigated. This type of motor is based on the combination of a rocket and air-breathing engines (ramjet and/or scramjet) and could, in the future, allow intra and extra-atmospheric flight at hypersonic speed. The aim of this paper was to demonstrate how the HyPrSpace technology was the most advantageous for the realization of such an engine. Thus, a comparative study allowed to affirm that the hybrid propulsion had many benefits over its propulsive competitors and seemed capable of meeting the needs required by the various military missions. The continuation of the study was based on an analysis of the operation and performances of a ramjet engine. The first part studied the influence of a supersonic inlet over its performances and another on an overall thermodynamic study of the engine. These results were used, later, for the realization of an in-house code whose goal consisted in the comparison of the trajectory of a missile propelled by a solid engine and that of a missile propelled by a RBCC one.